Specific Methods and Directions of Folk Epic Schools - Utayev Asror (Genius Publishing Group, 2022)
The description of folklore in the fine arts of Uzbekistan is based on the Uzbek schools of folk poetry and its spiritual foundations, its place in our national values, historical significance, relevance of the art of baxshi, epic and epic poetry. 'navi-national achievements, talked about. The distinctive aspects of the schools of epics are revealed in a comprehensive way
Keywords: Bakhshi; Classical Poetry; Romantic Epics; Hero